Climate-driven differences in flow regimes alter tropical freshwater ecosystems with consequences for an endemic shrimp - Tingley, Ralph W.; Infante, Dana M.; MacKenzie, Richard A.; Strauch, Ayron M.; Foulk, Patra B.; Roth, Brian (Frontiers in Ecology and Evolution, 2024)
Climate-driven shifts in the natural flow regime can threaten species persistence in stream systems, and anticipating such shifts before they occur is critical for conservation. We can explore how climate change may impact biota by examining natural systems that differ in terms of climate yet are similar in terms of other landscape features such as geology, size, and elevation. Across an established precipitation and hydrologic gradient on the east coast of Hawaii Island, we sampled stream habitat and populations of the endemic migratory mountain shrimp Atyoida bisulcata over three years and examined how habitat as well as population metrics and individual condition respond to differences in stream flow. Along the precipitation gradient, baseflow declined and streams shifted from run/riffle systems with moss cover to those with predominately pools and limited available habitat. Across years, baseflow conditions were relatively consistent within streams while measures of stream flow stability and the duration of high flows were more variable. Streams with high and persistent baseflow had greater atyid biomass density with larger individuals less prone to disease. Within-stream interannual variation in baseflow was low relative to differences across streams, and most A. bisulcata metrics also had low within-stream interannual variability, making average baseflow an appropriate surrogate for differences in suitability. However, extremes in annual rainfall may result in high variability in A. bisulcata metrics within a single stream due to seasonal drying or persistent high flows, highlighting the importance of long-term monitoring to fully understand population responses to climate-mediated stream flow. Our study suggests that changes in rainfall patterns will alter stream flow and may ultimately negatively influence tropical stream organisms.